Research on the evaluation of Chinese intelligent manufacturing policy under the four-dimensional analysis framework - Wang Jun; Wang Baomin (ITM Web of Conferences, 2025)
This paper utilizes the entropy TOPSIS method to evaluate the effectiveness of China's intelligent manufacturing policies under a four-dimensional analysis framework, which encompasses policy objectives, policy intensity, policy tools, and policy subjects. By selecting the intelligent manufacturing-related policy texts released between 2015 and 2024, this study aims to identify deficiencies and provide references for subsequent policy adjustments and formulations. Through empirical analysis, the echelon differences in policy evaluation results are revealed. The findings contribute to a deeper understanding of China's intelligent manufacturing policies and provide suggestions for future policy-making.